2005
DOI: 10.1002/cbf.1256
|View full text |Cite
|
Sign up to set email alerts
|

The effects of enalapril maleate and cold stress exposure on tyrosine hydroxylase activity in some rat tissues

Abstract: Enalapril is a highly specific and competitive inhibitor of angiotensin-I converting enzyme (ACE) and thus belongs to the category of ACE inhibitors. The beneficial effects of ACE inhibitors appear to result primarily from the suppression of the plasma renin-angiotensin-aldesterone system. This study was designed to detect the effects of enalapril maleate and cold stress on tyrosine hydroxylase (TH) activity in adrenal medulla, heart and hypothalamus in rat. In cold stress treatment (exposed to 8 degrees C col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Tyrosine, the precursor of catecholamines (the sympathetic nervous system (SNS) neurotransmitters such as dopamine, noradrenaline, and adrenaline), was significantly decreased, whereas homovanillate, a catecholamine product, was increased in the urine samples of animals exposed to cold stress. These alterations indicate enhanced SNS activity, leading to an up-regulated catecholamine metabolic pathway (Figure A), and is in agreement with previous reports of increased levels of plasma catecholamines (noradrenaline and adrenaline) and activated tyrosine hydroxylase (which catalyzes tyrosine to dopa) in tissues of animals exposed to cold stress . Increased SNS activity during cold stress contributes to a number of instant physiologic effects such as rapid heart rate, tensed muscles, constricted peripheral vasculature, and increased alertness.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Tyrosine, the precursor of catecholamines (the sympathetic nervous system (SNS) neurotransmitters such as dopamine, noradrenaline, and adrenaline), was significantly decreased, whereas homovanillate, a catecholamine product, was increased in the urine samples of animals exposed to cold stress. These alterations indicate enhanced SNS activity, leading to an up-regulated catecholamine metabolic pathway (Figure A), and is in agreement with previous reports of increased levels of plasma catecholamines (noradrenaline and adrenaline) and activated tyrosine hydroxylase (which catalyzes tyrosine to dopa) in tissues of animals exposed to cold stress . Increased SNS activity during cold stress contributes to a number of instant physiologic effects such as rapid heart rate, tensed muscles, constricted peripheral vasculature, and increased alertness.…”
Section: Discussionsupporting
confidence: 91%
“…1 It has been reported that cold stress, commonly occurring in clammy weather for human beings, is closely connected with cardiovascular and respiratory diseases, chilblain, diarrhea, and so forth, thereby causing higher mortality, especially among the elderly. 2 Numerous works have centered on individual gene expression, protein structure, and function, 3,4 as well as conventional pathophysiological studies on the hypothalamicpituitary-adrenal (HPA), neuroendocrine, circulatory systems, and immunological responses. 5 Panax ginseng is a highly favored herb restorative in many countries, particularly in China, as it possesses a variety of beneficial anti-inflammatory, antioxidant, glycolipid metabolic, and anti-cancer effects.…”
Section: Introductionmentioning
confidence: 99%
“…30 Interestingly, Bregonzio et al and Talas and Yurekli have shown that angiotensin receptor blockers and enalapril treatment were able to prevent the increase of tyrosine hydroxylase activity in the adrenal medulla of rats exposed to cold stress, suggesting a possible attenuation of insulinmediated inhibition of noradrenaline release by these treatments. 16,31 Our data from the present study showed that plasma insulin response to neuroglucopenic stress was modified by enalapril treatment although no significant change in the hyperglycaemic stress response could be observed. We postulate that the chronic treatment with enalapril might have attenuated the sympathetic effect on insulin secretion, very likely by potentiating glucoseinduced insulin secretion in this experiment.…”
Section: Discussionmentioning
confidence: 49%
“…Different mechanisms could underlie the enalapril‐induced changes in glucose metabolism during restraint. Studies have suggested that enalapril prevents increase in tyrosine hydroxylase activity in the adrenal medulla of rats exposed to cold stress and, thus, it could have attenuated the noradrenaline‐mediated inhibition of insulin release in enalapril‐treated rats submitted to restraint in the present study. Alternative mechanisms may be involved in this regulation, especially those related to the primary effects of RAS inhibitors in reducing angiotensin II levels and increasing levels of both bradykinin and angiotensin‐(1–7) .…”
Section: Discussionmentioning
confidence: 52%